Mechanistic studies of miR-582-3p targeting of PTPRCAP affecting lung adenocarcinoma via the Wnt/β-catenin pathway - Yang, Yuting; Zhao, Song; Han, Xiaoli; Guo, Pengfei; Zhao, Baoshan; Liang, Zongying (Frontiers in Oncology, 2025)
ObjectiveTo investigate the regulatory mechanism by which MicroRNA-582-3p (miR-582-3p) targets protein tyrosine phosphatase receptor type C-associated protein (PTPRCAP) and modulates Wnt/β-catenin signaling in lung adenocarcinoma pathogenesis.MethodsBioinformatics analysis of TCGA data assessed miR-582-3p expression and its clinicopathological relevance in LUAD. PTPRCAP mRNA and protein levels were evaluated via RT-qPCR and immunohistochemistry. The miR-582-3p-PTPRCAP interaction was validated using TargetScan8.0 and dual-luciferase reporter assays. Functional assays (CCK-8, scratch, Transwell) determined the effects of miR-582-3p and PTPRCAP on LUAD cell proliferation, migration, and invasion. Western blotting analyzed Wnt/β-catenin pathway components (β-catenin, GSK3β, p-GSK3β).ResultsmiR-582-3p was significantly upregulated in LUAD tissues and cell lines (A549, H1299), correlating with advanced disease features. PTPRCAP, a predicted target of miR-582-3p, showed reduced expression in LUAD. Dual-luciferase assays confirmed miR-582-3p directly binds the PTPRCAP 3′-UTR (P < 0.05). Overexpressing miR-582-3p suppressed PTPRCAP, enhanced malignant phenotypes (P < 0.05), and activated Wnt/β-catenin signaling (increased β-catenin and p-GSK3β; decreased GSK3β). Conversely, PTPRCAP overexpression inhibited tumorigenic behaviors and Wnt pathway activity. Rescue experiments demonstrated that PTPRCAP restoration counteracted miR-582-3p–mediated oncogenic effects (P < 0.05).ConclusionOur findings reveal a novel miR-582-3p/PTPRCAP/Wnt/β-catenin axis in LUAD progression, where miR-582-3p drives tumor growth by silencing PTPRCAP and activating Wnt signaling. These results highlight miR-582-3p as a potential therapeutic target and PTPRCAP as a tumor suppressor in LUAD, offering new insights for targeted intervention strategies.